Writing Skills for Parents - Yates, Irene (Piccadilly Press Ltd, 1996)
Writing Skills for Parents discusses the technicalities of writing - spelling, punctuation and grammar - and shows how parents can help their children to improve.
Keywords: Children-Parents-Writing-Learning-Nonfiction